Soil–pile interaction considering structural yielding: Numerical modeling and experimental validation. (15th September 2015) - Kampitsis, Andreas E.; Giannakos, Spyros; Gerolymos, Nikos; Sapountzakis, Evangelos J.
Highlights: Advanced fiber beam model for the inelastic analysis of pile-foundations. Beam model validation against a unique series of Laboratory Pushover tests. Experimental simulation with advanced nonlinear 3D FE model. Computational efficiency of beam formulation verified through comparison with 3D FE model. Abstract: In the present study the accuracy of an efficient beam formulation for inelastic analysis of pile-foundation systems is validated against a series of Laboratory Pushover tests on vertical single piles embedded in dry sand under different load paths to failure in M – Q space conducted in the Laboratory of Soil Mechanics/Dynamics (LSMD) in NTUA. The obtained results are also compared to those from a fully 3D Nonlinear Finite Element (FE) simulation. The proposed beam formulation is based on the Boundary Element Method (BEM) accounting for shear deformation effect. A displacement based procedure is employed and inelastic redistribution is modeled through a distributed plasticity (fiber) model exploiting pile material constitutive laws and numerical integration over the cross-sections, while the surrounding soil is modeled through independent inelastic Winkler springs. The efficiency of the beam formulation is verified through the good agreement between the measured and the calculated results.